Hydrographic and climatological conditions in the southern Caribbean of Costa Rica during El Niño 2014-2016 - Brenes-Rodriguez, Carlos Luis; Benavides-Morera, Rosario; Salazar Ceciliano, Juan Pablo; Alvarado-Gamboa, Luis Fernando (Revista Ciencias Marinas y Costeras, 2017)
In May, June, September and October 2014 and June, August, September and November 2015, hydrographic campaigns were carried out in the Southern Caribbean of Costa Rica in order to determine the influence of the El Niño phenomenon on this region. With a conductivity, temperature and depth profiler, temperature, salinity and chlorophyll a were determined in 23 stations. The surface temperature was between 26.6-30°C, surface salinities between 29-33.5 UPS, and surface chlorophyll a varied between 1.1 mg m-3-0.1 mg m-3. There is a thin mixture layer (T ~ 29°C), which did not exceed 20 m depth in 2014 and extended to 40 m in September and November 2015. The thermohaline indexes of the Caribbean Surface Water presented a significant decrease in its salinity by dilution due to El Niño and a slight increase in its temperature. The analysis between a temporal series of sea surface temperature at a point 15 km off Cahuita and the Oceanic Niño Index (ONI), determined that the area under study has a warm-up signal with a lag of 7 months following the presence of El Niño in the Tropical Pacific Ocean. During the 2014-2016 El Niño the studied area presented in some months precipitation that exceeded the climatological value by more than 50%.